2019
DOI: 10.1371/journal.pone.0217300
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of ionotropic L-Glutamate receptors in aged sensory neurons of Aplysia californica

Abstract: The simplified nervous system of Aplysia californica ( Aplysia ) allows for detailed studies of physiological and molecular changes in small sets of neurons. Sensory neurons of the biting and tail withdrawal reflexes are glutamatergic and show reduced L-Glutamate current density in aged animals, making them a good candidate to study age-related changes in glutamatergic responses. To examine if changes in ionotropic L-Glu receptor (iGluR) transcription underlie redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Relaxation caused by linalool was expected, as this monoterpenoid has depressant activity in fish (Rhamdia quelen and Cyprinus carpio) and shrimp (Litopenaeus vannamei) species (Becker et al 2015, Heldwein et al 2014, Taheri Mirghaed et al 2016). In addition, linalool is also known to act on the nervous system of mammals and rodents through mechanisms of action that include inhibition of glutamatergic receptors (Aprotosoaie et al 2014), which can also be found in gastropods (Greer et al 2019). Compared to other natural compounds previously tested in this species, linalool is as effective as eugenol (both promoted 100% relaxation) and more effective than the O. americanum EO (70%) and Origanum majorana EO (80%).…”
Section: Discussionmentioning
confidence: 91%
“…Relaxation caused by linalool was expected, as this monoterpenoid has depressant activity in fish (Rhamdia quelen and Cyprinus carpio) and shrimp (Litopenaeus vannamei) species (Becker et al 2015, Heldwein et al 2014, Taheri Mirghaed et al 2016). In addition, linalool is also known to act on the nervous system of mammals and rodents through mechanisms of action that include inhibition of glutamatergic receptors (Aprotosoaie et al 2014), which can also be found in gastropods (Greer et al 2019). Compared to other natural compounds previously tested in this species, linalool is as effective as eugenol (both promoted 100% relaxation) and more effective than the O. americanum EO (70%) and Origanum majorana EO (80%).…”
Section: Discussionmentioning
confidence: 91%
“…Animal age in this study was determined by the chronological age as well as the significant decline in performance of reflex behaviors beginning at the age of 12 months ( Figure 2 ). Our laboratory demonstrated that performance in these behaviors declines in a predictable manner with age ( Kempsell and Fieber, 2014 ) and that declining performance is accompanied by a decline in excitability of PVC sensory neurons that control tail withdrawal, decreased short-term facilitation (STF) between tail sensory and motor neurons ( Kempsell and Fieber, 2015 ), decreased expression of ionotropic glutamate receptor subunits ( Greer et al, 2019 ), and other changes in gene expression that alter proteostasis and increase neuro-inflammation ( Kron et al, 2020 ; Kron and Fieber, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…These alterations could lead to an increase in inhibitory response, such as seen in an octopaminergic manner for Caenorhabditis elegans in the case of npr-15 [ 69 ] with increased inhibition of neurons inside the reflex circuitry. Furthermore, reduced glutamatergic excitatory transmission via downregulation of the AMPA receptor may lead to decreased neuron excitability in Aplysia [ 38 , 70 ], resulting in less firing of motoneurons for prolonged foot muscle contraction. DE of receptors involved in neurotransmission can therefore lead to the decreased TWR duration caused by acidification.…”
Section: Discussionmentioning
confidence: 99%